Associations of various exercise types with health-related physical fitness: Focus on physical fitness age - Zhennan Wang; Takehiko Tsujimoto; Kyohsuke Wakaba; Ryoko Mizushima; Hiroyuki Kobayashi; Kiyoji Tanaka (Japanese Society of Physical Fitness and Sports Medicine, 2020)
The health-related physical fitness status of habitual exercisers with different exercise types has not been adequately described previously. Therefore, we aimed to evaluate the various benefits in health-related physical fitness associated with participation in various exercises. The study was a cross-sectional study on 164 Japanese adult males (age: 45-80 years), who were classified into seven groups according to their most frequently practiced exercise: non-exercisers (n = 48), walking (n = 38), jogging (n = 23), rhythm calisthenics (n = 13), bowling (n = 20), tennis (n = 13), and cycling (n = 9). Anthropometric and health-related physical fitness data were measured, and exercise habit was investigated using a questionnaire survey. Physical fitness age (PFA) was estimated in all study participants. Compared to 48 non-exercisers, joggers obviously had superior cardiorespiratory endurance (maximal oxygen uptake: 45.5 ± 1.1 mL/kg/min). Tennis players showed better flexibility (trunk flexion: 6.8 ± 2.5 cm), agility (side-to-side stepping: 39.8 ± 1.6 reps), balance (one-legged stand with eyes closed: 24.9 ± 3.3 s), and lower-limb strength (vertical jump: 38.9 ± 1.6 cm). The difference between chronological age and PFA was approximately 13 years in joggers, 10 years in tennis players, and 5 years in rhythm calisthenics practitioners, all of which were significantly better when compared to the difference in non-exercisers. Various exercises appeared to confer different advantages on health-related physical fitness status. Exercise type with different skills was considered as a factor to maintain or promote physical fitness for habitual exercisers, especially older individuals.